Would you believe ... Vatican City is a country?! and other metroplitan marvels - Platt, Richard 1953- (Would you believe ..., 2010)
Find out about medieval towns and the extreme cities in the jungle and polar regions. What is suburban bliss and why are some of our cities dying? Read this book from start to finish for a riveting social history or dip in and out for some fascinating and often hilarious facts